Hyperthermic intracavitary nanoaerosol therapy (HINAT) as an improved approach for pressurised intraperitoneal aerosol chemotherapy (PIPAC): Technical description, experimental validation and first proof of concept - Göhler, Daniel; Große, Stephan; Bellendorf, Alexander; Falkenstein, Thomas Albert; Ouaissi, Mehdi; Zieren, Jürgen; Stintz, Michael; Giger-Pabst, Urs (Beilstein Journal of Nanotechnology, 2017)
Background: The delivery of aerosolised chemotherapeutic substances into pressurised capnoperitonea has been reported to be more effective than conventional liquid chemotherapy for the treatment of peritoneal carcinomatosis. However, recent reports reveal limitations of the currently available technology.Material and Methods: A novel approach for pressurised intraperitoneal aerosol chemotherapy (PIPAC), called hyperthermic intracavitary nanoaerosol therapy (HINAT), based on extracavitary generation of hyperthermic and unipolar charged aerosols, was developed. The aerosol size distribution, the spatial drug distribution and in-tissue depth penetration of HINAT were studied by laser diffraction spectrometry, differential electrical mobility analysis, time of flight spectrometry, scintigraphic peritoneography and fluorescence microscopy. All experiments were performed contemporaneous with conventional PIPAC for the purpose of comparison. Furthermore, a first proof of concept was simulated in anesthetised German Landrace pigs.Results: HINAT provides a nanometre-sized (63 nm) unipolar-charged hyperthermic (41 °C) drug aerosol for quasi uniform drug deposition over the whole peritoneum with significantly deeper drug penetration than that offered by conventional PIPAC.
Keywords: HINAT; intracavitary; intraperitoneal; nanoaerosol; PIPAC; pressurized; therapy